Pengaruh Struktur Modal dan Faktor Eksternal terhadap Nilai Perusahaan (Studi pada PT. Bank Central Asia, Tbk) - Muhammad Fuad; Ayu Wandari (Jurnal Manajemen dan Keuangan, 2018)
The research aims to analyze the influence of capital structure and external factors on firm value. Object of research at PT. Bank Central Asia, Tbk, with the 2007-2016 financial periods. Capital structure is represented by debt to equity ratio (DER); external factors tested include inflation, interest rates and exchange rates; as well, company value is measured using price to book value (PBV). Data analysis method uses multiple linear regression (MRA). Four partial hypotheses were tested using t-test, while one simultaneous hypothesis was tested using F-test. The regression analysis results stated that capital structure, inflation and exchange rate had a negative influence on firm value; while interest rates have a positive influence on firm value. Furthermore, capital structure has a dominant influence on firm value. Hypothesis test results showed that all independent variables have an insignificant effect on firm value as dependent variables, both partially and simultaneously. The coefficient of determination showed the independent variables analyzed in this research model contribute relatively high in explaining the variance that occurs in the firm value of PT Bank Central Asia, Tbk.